A Content Analysis of the Philosophical Foundations of the Islamic Religious Education Curriculum - Hidayati, Sri; Kemerindo, Gref; Yakub, Ramli; Fadli, Rahmat; Lahmi, Ahmad (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
The development of an Islamic Education curriculum requires a strong philosophical foundation so that it does not become limited to technical-administrative aspects. This article aims to explain the relationship between foundational philosophy, institutional vision and mission, and their implementation in designing the Islamic Religious Education curriculum. This study employs a qualitative method with a content analysis approach using various literature sources that discuss educational policy, curriculum theory, and implementation practices in Islamic educational institutions. The analysis indicates that the philosophy of Islamic education serves as the basis for formulating learning objectives oriented toward Tauhid values and character formation. The vision and mission function as a bridge between philosophical values and the operational direction of the curriculum. In addition, the development of curriculum components such as objectives, content, methods, and evaluation requires principles of relevance, flexibility, continuity, efficiency, and effectiveness. The review of practices in Madrasah Aliyah and Vocational High Schools suggests differences in implementation emphasis according to each institution’s context. These findings indicate that the alignment between foundational philosophy, vision and mission, and curriculum structure is essential for producing a more adaptive and contextually relevant Islamic Religious Education curriculum.